AVALIAÇÃO DE ATRIBUTOS QUE INTEGRAM O PLANEJAMENTO DE CIDADES SUSTENTÁVEIS E INTELIGENTES: APLICAÇÕES EM CAMPO GRANDE (MS) - Mário Cesar Junqueira de Oliveira (2021)
The rapid urbanization places cities in a central position to solve urgent global issues, such as environmental and sanitary crisis. At the same time, cities must keep the appropriate level of the essential public services and promote the quality of life for the whole urban population, with unlimited resources. The urbanization cannot be seen only as a demographic phenomenon, but also as a process of transformation capable to motivate the sustainable urban development and, in times of rapid digitalization and technological development, urban smartness. Thereby, Smart Sustainable Cities have been receiving special highlight in the development agendas of several nations, for instance Brazil, like the city of Campo Grande, the capital of the state of Mato Grosso do Sul (MS), which is experiencing increasing rates of urbanization. The development of Smart Sustainable Cities, among other factors, is led to an integrated territorial planning that promotes the mixed land usage, the urban green areas distribution, as well as promoting cycle way structure that led to cycling and equity of access to the public transportation. The principles and the Guidelines of the 2030 Agenda and the United Nations’ New Urban Agenda point to the same perspectives of city construct models. Thus, the objective of this work is to evaluate the mixed land uses, distribution of urban green areas, cycle way structure and access to the public transportation service in Campo Grande (MS) as attributes of urban planning to its development as Smart Sustainable City. For this purpose, four urban indicators were applied, evaluated in its seventy-four neighborhoods and seven Urban Regions of Campo Grande (MS). The results revealed favorable aspects in the evaluation, with the mixed land use index of 0,527, it is considered an average value, urban green areas represent 6,4%, cycle way structure of 2,8% and 96,1% of the homes at a walking distance of up to 600 meters from the bus stops, values higher than the ones consulted in the bibliography. However, the capital of the state of Mato Grosso do Sul still lacks adequate urban planning, in terms of equal distribution of the evaluated indicators in the different neighborhoods, that guarantees the mixed land uses, distribution of urban green areas and accessible and sustainable transportation system for all, promoting its development as Sustainable and Smartness City and reach the principles of the 2030 Agenda and the New Urban Agenda.